Marx e a divisão do trabalho no capitalismo - Barradas, Liana França Dourado (2012)
This dissertation makes a systematization form analysis of the marxian on processuality historical division of labor in capitalist society. Through analysis of the immanent Book first, T. I and II of the celebrated work of Karl Marx's Capital: critique of political economy sought to expose the general aspects of the social division of labor concomitant development work. Demonstrate that for Marx, the process of development of the social division of labor has a universal character, but throughout history unfolds with different characteristics in different class societies, as in slavery, feudalism and capitalism. We will also see that the social division of labor is crucial in the process of generalization of good production. We will review the general and specific aspects of the division of labor as the driving force for progress of productive forces in the capitalist mode of production, and as a specific form of consolidation of exploitation of capital over labor. For Marx, the development of the division of labor under capitalism opposes the intellectual forces of the production process as the property of others for producers who perform manual labor. The capital, accordingly, exercising despotic power to dominate and direct the intellectual powers of production. This process of division between manual and intellectual work begins in simple co-operation, develops and manufactures complete in the industry to consolidate large separation between work and science as a force serving the interests of capital. Thus, according to Marx, we see that processuality historical division of labor under capitalism fulfill the social role to play in the productive sphere and in society at large command of capital over labor process and on producers.